Framing research in social development thinking and practice the DSD experience - Barrameda, Teresita Villamor (2019)
This study examines the trends in social development (SD) perspectives, strategies, and processes gleaned from the dissertations of doctoral graduates of the UP-CSWCD Doctor of Social Development (DSD) program from 2014-2019. Thirteen (13) dissertations of DSD graduates were used as case materials in drawing out lessons in SD research.
Two major trends emerged from the 13 dissertations: one, what are the defining features of SD research, and two, knowledge-building and meaning-making initiatives. Two guiding features differentiate SD research from mainstream social research: (1) a clear standpoint and bias for the poor, marginalized, and disadvantaged groups and communities; and (2) privileging the voices and perspectives of the poor, the marginalized, and the disadvantaged.
In terms of knowledge-building and meaning-making, significant themes were noted: (1) community organizing-community development (CO-OD) perspectives are embedded in SD concepts, strategies, and processes; (2) feminist perspectives complement and enhance SD knowledge building by examining gender and power relations within social institutions (i.e. family, community organizations, market, and the State); and, (3) the dissertations provide a learning platform for DSD students to engage in development discourse and grounded theorizing. The research participants are generally regarded as co-learners in the research process. The paper concludes by citing the implications and challenges to Social Development as an academic discipline in the context of policy development and planning, theorizing, and curricular development and enhancing.